The Strengths And The Weaknesses Of The Administrative Reform Efforts In Turkey - Çetin, Zuhal Önez (European Scientific Journal, ESJ, 2016)
The administrative reform that is determined with all attempts having the objective of attaining the administration to a scheme that could make contributions to accomplish the national targets, provide to meet the public services in a cost-saving, rapid, effective and qualified way, had a long history in Turkey. In that framework, while the administrative reform has a long history, public administration system in Turkey still confronted with the problem of not having a systematic and integrated administrative reform process. Within the context of the study, the administrative reform efforts have been examined at four periods; such as reform efforts before planned period, reform efforts at planned period, reform efforts at the 1980s, and administrative reform efforts at the last period. At that framework, the significant Report, Projects and Plans such as MEHTAP (The Central Government Organization Research Project), KAYA (Public Administration Research Project), Preliminary Report on Administrative Reform and Reorganization (1961), Administrative Reform Advisory Board Report, Five-year Development Plans have been critically searched to indicate the strengths and weaknesses of those reform initiatives. Finally, as a concluding remark, some proposals have been put forth to shed light on a systematic and proper application of the administrative reform process in Turkey.